Preparation and application of single-atom nanozymes in oncology: a review - Liang, Huiyuan; Xian, Yijie; Wang, Xujing (Frontiers in Chemistry, 2024)
Single-atom nanozymes (SAzymes) represent a cutting-edge advancement in nanomaterials, merging the high catalytic efficiency of natural enzymes with the benefits of atomic economy. Traditionally, natural enzymes exhibit high specificity and efficiency, but their stability are limited by environmental conditions and production costs. Here we show that SAzymes, with their large specific surface area and high atomic utilization, achieve superior catalytic activity. However, their high dispersibility poses stability challenges. Our review focuses on recent structural and preparative advancements aimed at enhancing the catalytic specificity and stability of SAzymes. Compared to previous nanozymes, SAzymes demonstrate significantly improved performance in biomedical applications, particularly in tumor medicine. This progress positions SAzymes as a promising tool for future cancer treatment strategies, integrating the robustness of inorganic materials with the specificity of biological systems. The development and application of SAzymes could revolutionize the field of biocatalysis, offering a stable, cost-effective alternative to natural enzymes.